Management of Various Sources of Hazardous Waste - Nor Azalina, Rosli; Hamidi, Abdul Aziz; Leonard Lim, Lik Pueh; Inawati, Othman; Mohd Hafiz, Zawawi; Yung-Tse, Hung (Springer Nature, 2024)
The generation of hazardous waste has escalated as a result of industrialization to meet the ever-growing demand due to rapid development and population growth. The development of new industries, agricultural practices, and processing techniques can produce emerging hazardous wastes that might not be listed in the environmental regulations. Both increasing generation rate and the nature of hazardous wastes are among the major influences shaping the management of hazardous waste, from the formulation of environmental regulations to the implementation of waste management options. A key to effective hazardous waste management at the source is the competency to identify and characterize hazardous waste upon a generation to facilitate the proper handling, treatment, and disposal of the hazardous waste with reference to the relevant regulations. The USEPA, under the Code of Federal Regulations (CFR), simplified waste determination by classifying industrial wastes into codes of F, K, P, and U based on the characteristics, sources, industrial processes, or generation rate of the hazardous waste. In Malaysia, hazardous wastes are enlisted as scheduled wastes under the Environmental Quality (Scheduled Wastes) Regulations 2005, categorized based on the general characteristics and content of wastes. The waste management hierarchy is a typical principle for formulating a hazardous waste management system and facilitating the selection of waste management options based on the waste policy and programs by the government and industry. The approaches and implementation in several countries on hazardous waste management, including from agricultural sources, are discussed in this chapter.